Toward a more efficient organ placement system (and defeating FOMO). Issue 6 (28th February 2022) - Roll, Garrett R.; Hirose, Ryutaro
Abstract : Rational use of offer filters holds the promise of a more efficient kidney placement system. See King et al. (Page 1593 )